Mirʾāt al-adwār wa-mirqāt al-akhbār. Volume 2 - Lārī, Muṣliḥ al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Muṣliḥ al-Dīn Lārī (d. 979/1572) was a Persian scholar in the traditional and foreign sciences. Born in Luristan in south-western Iran, he received his academic education in Shiraz, attending the lectures of Ghiyāth al-Dīn Dashtakī ((d. 949/1542) and Kamāl al-Dīn Lārī (d. 979/1572), prominent representatives of the Shiraz School in philosophy. Under the Safavids, many intellectuals left Persia for India or Asia Minor. Lārī went to India, living at the court of the Mughal emperor Humāyūn (d. 963/1556). After the latter's death he went to Mecca and then on to Istanbul, where he lived for a number of years, a respected scholar among his peers. His final years Lārī spent as the head of a school in Amīd, today's Diyarbakır. Lārī compiled the universal history published here in Istanbul, dedicating it to Sultan Selim II (d. 982/1574). Worthy of note are his lack of partisanship, his transparence on sources, and his interest in scholars and artists. 2 vols; volume 2.